Prediktori vremenski zavisnog preživljavanja kod bolesnika sa septičkim šokom liječenih ekstrakorporalnim pročišćavanjem krvi: parametrijska analiza preživljavanja - Momcicevic, Danica; Vucicevic, Katarina; Spiric, Nikolina; Zlojutro, Biljana; Jandric, Milka; Dragic, Sasa; Sobot, Nikola; Kovacevic, Tijana; Kovačević, Peđa (Journal of Medical Biochemistry, 2026)
Background: Sepsisremains associatewith high mortality despite advances in organ support, including extracorporeal blood purification. Conventional prognostic tools rely on static endpoints and do not capture dynamic mortality risk. We aimed to identify predictors of time-dependent survival in sepsis patients. Methods: We conducted a retrospective, single-center study of adults with sepsis or septic shock treated with continuous renal replacement therapy incorporating CytoSorb® or oXiris®. Demographic, clinical, and laboratory data were extracted. Survival was analyzed using Kaplan–Meier estimates, Cox proportional hazards regression, and parametric survival models. Multivariable analyses estimated independent effects, and the final parametric model was used to derive survival probabilities and median survival times conditional on covariates. Results: Among 94 patients, 42 deaths occurred. In multivariable Cox analysis, higher D-dimer, lactate (Lact), and SAPS II were independent predictors: each 10 µg/mL increase in D-dimer was associated with a 15% higher hazard, each 1 mmol/L increase in Lactwith 12%, and each 1-point increase in SAPS II with 3% higher hazard. The log-normal parametric model confirmed these predictors were associated with shorter expected survival. Conclusions: D-dimer, lactate, and SAPS II independently predict mortality in ICU patients with sepsis or septic shock undergoing extracorporeal blood purification. These findings provide a dynamic, quantitative framework for risk stratification and clinical decision-making. Prospective multicenter studies are needed to validate these results.